2023
DOI: 10.1038/s42003-023-04727-z
|View full text |Cite
|
Sign up to set email alerts
|

Sub-millisecond conformational dynamics of the A2A adenosine receptor revealed by single-molecule FRET

Abstract: The complex pharmacology of G-protein-coupled receptors (GPCRs) is defined by their multi-state conformational dynamics. Single-molecule Förster Resonance Energy Transfer (smFRET) is well suited to quantify dynamics for individual protein molecules; however, its application to GPCRs is challenging. Therefore, smFRET has been limited to studies of inter-receptor interactions in cellular membranes and receptors in detergent environments. Here, we performed smFRET experiments on functionally active human A2A aden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…In summary, the conformational energy landscape of ACKR3 is flatter and has more local minima reflecting its greater conformational heterogeneity than CXCR4 or other previously studied GPCRs 37,38,40 . The structural heterogeneity is consistent with the ability of ACKR3 to bind and be activated by different ligands via a distortion mechanism, and the fact that most ligands are activating rather than inhibiting.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In summary, the conformational energy landscape of ACKR3 is flatter and has more local minima reflecting its greater conformational heterogeneity than CXCR4 or other previously studied GPCRs 37,38,40 . The structural heterogeneity is consistent with the ability of ACKR3 to bind and be activated by different ligands via a distortion mechanism, and the fact that most ligands are activating rather than inhibiting.…”
Section: Discussionmentioning
confidence: 85%
“…For example, smFRET studies of the β2 adrenergic receptor (β2AR) revealed a dynamic equilibrium between inactive and active conformations that was responsive to agonist and G protein binding 37 . More recent smFRET studies of the glucagon receptor 38 and the A2A receptor (A2AR) 39,40 have revealed the existence of stable intermediate conformations in addition to inactive and active receptor conformations. Similar to these studies, our system allows real-time observation of the conformational fluctuations of individual receptors in a native-like lipid environment, and assessment of the differences in the conformational dynamics of CXCR4 and ACKR3 in their apo states and in response to ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we previously showed that the full agonist NECA does not show any binding to the A 2A -PSB1-bRIL construct (at concentrations of up to 3 mM, determined vs. the antagonist radioligand [ 3 H]MSX-2), whereas the affinity of antagonists and of the antagonist radioligand itself was unaffected. 9 It is worth noting that structures of NECA have been solved with 33,52 or without 53 G proteins. While intracellular rearrangements and especially the extent of the outward movement of helix VI are largely dependent on the presence of G proteins, the ligand binding pocket in these full agonist-bound structures is identical� independent of the presence of G proteins�and clearly distinct from the inactive receptor conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, NMR 18 and single-molecule Forster resonance energy transfer (smFRET) investigations of the A 2A AR in complex with LUF5834 revealed distinct conformations when compared to those found for NECA or the antagonist ZM241385. 53 However, the covalent β 2 -adrenergic receptor agonist FAUC50 54 as well as β 1 -adrenergic receptor agonists 55 were reported to stably bind to inactive conformations without G proteins present. Alternatively, the partial agonistic mechanism of action may also be explained by a combination of the above-mentioned principles 56 and may even be different for various GPCRs or ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation